Smart soil monitoring and water conservation using irrigation on technology - George Fernandez s; Vijayakumar K; Kalyanasundaram V; Vidyasagar S; Selvakumar K; Selvabharathi D; Palanisamy R (Institute of Advanced Engineering and Science, 2020)
The conventional system of irrigation how efficient and well managed it may be wastes up to 50% of the water supplied. purpose of this paper is to provide a user-oriented and standalone irrigation solution for soil monitoring and water conservation, based on network of sensor. Using the input from the user the system will act automatically. It not only reduce the water waste but also is cost efficient and easy to operate. Different parameters like soil moisture, temperature and humidity are imported in order to calculate the efficient quantity of water needed. This system uses different sensors like soil moisture sensor, humidity sensor and temperature sensor to take required data. In this paper, the proposed project uses sensor having low power consumption reducing load overall. The system also stores the input and uses it for forecasting. The concept of IoT is implied in this paper. The control of motors are automated powered by solar panels. The data is stored in table format. All data is accessible via internet. This system can help the user to gain vital data about the fields irrespective of the weather condition.